Efficacy and safety of rescue stenting following failed mechanical thrombectomy for anterior circulation large vessel occlusion: propensity score analysis. (17th September 2019) - Peng, Feng; Wan, Junfang; Liu, Wenhua; Huang, Wenguo; Wang, Li; Qiu, Tao; Yang, Shiquan; Shi, Qiang; Zhang, Shuai; Zeng, Guoyong; Wang, Yan; Ai, Zhibin; et al.
Abstract : Purpose: To evaluate the effectiveness and safety of rescue stenting (RS) after failed mechanical thrombectomy (MT) for patients with large artery occlusion in the anterior circulation. Methods: Consecutive patients who experienced failed reperfusion and subsequently did or did not undergo RS at 16 comprehensive stroke centers were enrolled from January 2015 to June 2018. Propensity score matching was used to achieve baseline balance between the patient groups. Symptomatic intracranial hemorrhage (sICH) at 48 hours and the modified Rankin Scale scores and mortality at 3 months in the two groups were compared. Results: A total of 90 patients with RS and 117 patients without RS after failed MT were enrolled. Propensity score matching analysis selected 132 matched patients. The good outcome rate was significantly higher in matched patients with RS than in those without RS (36.4% vs 19.7%, p=0.033), whereas the sICH (13.6% vs 21.2%, p=0.251) and mortality (31.9% vs 43.9%, p=0.151) were not significantly different between the groups. Conclusions: RS seems to be an effective safe choice for patients with large vessel occlusion of the anterior circulation who underwent failed MT.